Learning Style of Grade Eight Students: Basis on Enhancing Historical Thinking Skills Using Contextualized Learning Activities in Araling Panlipunan - Andal, Rose Ann E.; Hermosa, Jherwin P. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
This study aimed to craft contextualized learning activities based on student learning style with the evaluation of its effectiveness and the relationship with the perceived effectiveness of material to student historical thinking skills. This employed the descriptive correlational design of quantitative method as participated by 53 Grade Eight (8) respondents in San Isidro National High School who were chosen using the purposive sampling procedures. The data were gathered using pretest questionnaires, survey questionnaires, evaluation questionnaires, and posttest questionnaires which are validated with the help of the experts. Data communications were established before data gathering procedures and were analyzed using mean, standard deviation, and Pearson R. Findings revealed that the students prefer the visual learning style in studying Araling Panlipunan MELCS 1-8, the LA is generally agreed to be effective as to content in terms of adequacy (OWM=3.45, agree); coherence (OWM=3.44, agree); appropriateness (OWM=3.40, agree); and usefulness (OWM=3.43, acceptable). There was no significant relationship between the perceived effectiveness of the material and student’s historical thinking skills. The study recommends that to improve the efficiency of teaching and learning, Araling Panlipunan teachers may develop further their historical thinking abilities. This will also improve students' acquisition of these abilities.